2013
DOI: 10.1016/j.bbapap.2013.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic analysis of allosteric and non-allosteric effects arising from nanobody binding to two epitopes of the dihydrofolate reductase of Escherichia coli

Abstract: Although allosteric effector antibodies are used widely as modulators of receptors and enzymes, experimental analysis of their mechanism remains highly challenging. Here, we investigate the molecular mechanisms of allosteric and non-allosteric effector antibodies in an experimentally tractable system, consisting of single-domain antibodies (nanobodies) that target the model enzyme dihydrofolate reductase (DHFR) from Escherichia coli. A panel of thirty-five nanobodies was isolated using several strategies to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 28 publications
1
36
0
Order By: Relevance
“…Signals of the residues located at the contact surface with the nanobody show intensity loss, or chemical shift change, depending on the nanobody binding parameters. Crystal structures of several nanobody complexes with dihydrofolate reductase showed good agreement between NMR mapping and the x-ray structures (73).…”
Section: Nanobodies As Probes Of Fast Protein Dynamicsmentioning
confidence: 79%
“…Signals of the residues located at the contact surface with the nanobody show intensity loss, or chemical shift change, depending on the nanobody binding parameters. Crystal structures of several nanobody complexes with dihydrofolate reductase showed good agreement between NMR mapping and the x-ray structures (73).…”
Section: Nanobodies As Probes Of Fast Protein Dynamicsmentioning
confidence: 79%
“…Abs that stabilize one conformational state over another may be common 51,52,53,54,55 . The MOA may be rarely recognized since, in these cases, no notable conformational changes would be observed upon Ab binding and alternate conformations of the antigen may elude structural determination.…”
Section: Discussionmentioning
confidence: 99%
“…The structure of the complex was solved by molecular replacement using Phaser 62 . The structures of RTA (PDB 1J1M), 38 RTA1-33/44-198 (PDB 4IMV), 21 a sdAb (PDB 4FHB), 51 and the structure of the A3C8 sdAb (PDB 5SV4) were used as search models. Model-building was performed using Coot 63,64 .…”
Section: Methodsmentioning
confidence: 99%
“…This interesting observation opens up new, generalizable avenues for antibody-based inhibitors of enzymes and receptors [58]. Of particular interest to this review, the same group reported earlier [59] that allosteric effects, brought about by binding of antibody fragments, were due to conformational constraint and altered protein dynamics rather than epitope distortion, suggesting that the antibody fragments were locking out naturally sampled conformations rather than imposing unnatural perturbation.…”
Section: Enzyme Systems-links To Kineticsmentioning
confidence: 91%